Attitudes Towards Globalization Barriers and Implications for Voting: Evidence from Sweden - Leyla D. Karakas; Nam Seok Kim; Devashish Mitra (Center for Economic Studies and ifo Institute (CESifo), 2021)
Using six waves of the Swedish National Election Studies (SNES) survey data, we investigate the determinants of attitudes towards globalization barriers (trade and immigration) and how important these attitudes are in how people vote. In line with the existing results in the literature, we find that more educated and richer voters support freer trade and more immigration. We also find that conservative voters in Sweden are more likely to prefer freer trade but higher immigration barriers. Once various economic and demographic determinants of globalization barrier preferences along with voters' ideologies on a liberal-conservative spectrum are controlled for in the analysis of voting behavior, trade barrier preferences lose their statistical significance while attitudes towards immigration barriers remain significant. This suggests that immigration attitudes affect voting behavior through channels involving identity-driven factors that are different from the channels through which more traditional electoral issues, such as trade barriers, work. Focusing on the anti-globalization Swedish Democrats, we confirm that voters with a greater preference for barriers to immigration were more likely to switch their votes to this party from the 2014 to the 2018 election.
Keywords: D72; F16; J61; 330; globalization; trade; immigration; elections; voting; survey data; Sweden